The association of fibroblast growth factor 23 with atherosclerosis and arterial stiffness in peritoneal dialysis patients (Annals of Medical Research, 2021)
Aim: Increased serum fibroblast growth factor-23 (FGF-23) levels are associated with adverse cardiovascular events in chronic kidney disease patients. The aim of our study was to investigate the association of FGF-23 with atherosclerosis and arterial stiffness in patients with peritoneal dialysis (PD).Material and Methods: This cross-sectional study was performed in 55 (34 (61.8%) male/21 (38.2%) female) PD patients with a mean age of 53.1±11.4 years. The presence of atherosclerosis was determined by carotid artery-intima media thickness (CA-IMT) and the presence of arterial stiffness was determined by brachial-ankle pulse wave velocity (baPWV). Residual renal function was determined by residual glomerular filtration rate (rGFR), renal creatinine clearance (CCr), and residual urine output. FGF-23 and soluble klotho (s-KL) levels were determined by enzyme-linked immunosorbent assay.Results: CA-IMT (p 0.001), baPWV (p = 0.003 ), log10 FGF-23 (p 0.001) were higher and s-KL (p 2.16. In multiple regression analysis there was an inverse relationship between log10 FGF-23 and rGFR (p = 0.032), residual diuresis (p = 0.048), renal CCr (p = 0.045). There was no relationship with log10 FGF-23 and CA-IMT, baPWV (p > 0.05).Conclusion: Increased atherosclerosis and arterial stiffness were detected in PD patients compared to healthy subjects. There was no relationship between FGF-23 and atherosclerosis and arterial stiffness in PD patients.Keywords: Peritoneal dialysis; Fibroblast growth factor-23; Atherosclerosis; Arterial stiffness.
Keywords: Peritoneal dialysis; Fibroblast growth factor-23; Atherosclerosis; Arterial stiffness.